Micropatterned Down‐Converting Coating for White Bio‐Hybrid Light‐Emitting Diodes. (26th October 2016) - Niklaus, Lukas; Tansaz, Samira; Dakhil, Haider; Weber, Katharina T.; Pröschel, Marlene; Lang, Martina; Kostrzewa, Monika; Coto, Pedro B.; Detsch, Rainer; Sonnewald, Uwe; Wierschem, Andreas; Boccaccini, Aldo R.; et al.
Abstract : White hybrid light‐emitting diodes (WHLEDs) are considered as a solid approach toward environmentally sustainable lighting sources that meet the "Green Photonics" requirements. Here, WHLEDs with protein‐based down‐converting coatings, i.e., Bio‐WHLEDs, are demonstrated and exhibit worthy white color quality, luminous efficiency, and stability values. The coatings feature a multilayered cascade‐like architecture with thicknesses of 1–3 mm. This limits the efficiency due to the low optical transmittance. Thus, submillimeter coatings, where the location of the proteins is well‐defined, are highly desired. It is in this context where the thrust of this work sets in. Here, a straightforward way to design microstructured single‐layer coatings, in which the proteins are placed at our command by using 3D printing, is presented. Based on comprehensive spectroscopic and rheological investigations, the optimization of the matrix and the plotting to prepare different micropatterns, i.e., lines, open‐grids, and closed‐grids, is rationalized. The latter are applied to prepare Bio‐WHLEDs with ≈5‐fold enhancement of the luminous efficiency compared to the reference devices with a cascade‐like coating, without losing stability and color quality. As such, this work shows a new route to exploit proteins for optoelectronics, setting a new avenue of research into the emerging field of Bio‐WHLEDs. Abstract : The first example of bio white hybrid light‐emitting diodes (WHLEDs) with a micropatterned rubber‐like coating is presented. The excellent luminescent features of the proteins and the mechanical properties of the matrix allow for straightforward design of a down‐converting micropatterned coating prepared using a 3D plotting technique. Direct comparison with a cascade‐like bio‐WHLED shows that the use of micropatterned coating leads to a ≈5‐fold enhancement of the luminous efficiency without losing stability or color quality.